UPAYA MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN MELALUI TANGGA MANIK-MANIK MONTESSORI DI KELAS A TK ANGGREK KARANGPLOSO: EFFORTS TO IMPROVE THE ABILITY TO RECOGNIZE NUMBERS THROUGH MONTESSORI BEAD LADDER IN CLASS A OF ANGGREK KARANGPLOSO KINDERGARTEN - Ertanti, Devi Wahyu; Lailatul Maghfiroh, Nur (Thufuli : Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2021)
The purposed of this research was to improved recognized a numbers by the montessori method. For class A at Bina Anaprasa Kindergarten. This study used 25 children without children with special needs. The research method was classroom action research. Data collection techniques used observation, interviews and documentation. Analysis techniques were qualitative for analyzed cycles and qualitative for compared results. Data sources were the activitied of the teacher and the results of the development of recognized a numbers. The results of the study were the ability to recognized numbers increases. 24% in the first cycle and 76% in the second cycle. Learn was did by played. In accordance with the child's development and integrated thematic uses for other developments.